2019
DOI: 10.1111/imm.13124
|View full text |Cite
|
Sign up to set email alerts
|

Biological and clinical significance of T helper 17 cell plasticity

Abstract: Mature T helper (Th) effector cells originate following antigen recognition by naive T precursors. The maturation process is accompanied by the acquisition of specific effector functions that distinguish at least three different T helper subsets: Th1, Th2 and Th17. In general, maturation of somatic cells is accompanied by terminal differentiation. However, accumulating evidence shows that effector T cells retain a certain degree of plasticity. This is especially true for Th17 cells, which have been shown to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 99 publications
(208 reference statements)
1
65
0
Order By: Relevance
“…Inflammatory cytokines are important factors in deciding the fate of activated naive cells. In particular, cytokines such as IL-6 and IL-1b, in combination with TGF-b, may lead to enhanced differentiation toward the pathogenic T H 17 subset (53). In this regard, the increased IL-6 production observed with vitamin D treatment may also influence T cell differentiation to a phenotype that would be undesired in the context of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines are important factors in deciding the fate of activated naive cells. In particular, cytokines such as IL-6 and IL-1b, in combination with TGF-b, may lead to enhanced differentiation toward the pathogenic T H 17 subset (53). In this regard, the increased IL-6 production observed with vitamin D treatment may also influence T cell differentiation to a phenotype that would be undesired in the context of autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate PDT‐mediated activation of a type 3 immunity that leads to type 1 immunity via inflammation characterized by neutrophilia. The mechanism of this switch is unclear but may be related to the inherent plasticity of Th17 cells (87).…”
Section: Components Of Pdt: Photosensitizer Light and Molecular Oxygenmentioning
confidence: 99%
“…Moreover, fate-mapping experiments demonstrated that Th17 cells in the CNS co-express or exclusively express interferon (IFN)γ [23,24]. This led to the conclusion that Th17 cells can switch to an IFNγ-producing, ex-Th17 phenotype [25][26][27]. The molecular mechanisms of Th17 cell plasticity have been shown to be highly dependent on the tissue environment of the cells [26,[28][29][30][31][32][33], while the prerequisites shaping T cell phenotypes within the CNS tissue remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%